Quality of life after transcatheter or surgical aortic valve replacement using the Toronto Aortic Stenosis Quality of Life Questionnaire - Kennon, Simon; Styra, Rima; Bonaros, Nikolaos; Stastny, Lukas; Romano, Mauro; Lefèvre, Thierry; Di Mario, Carlo; Stefàno, Pierluigi; Ribichini, Flavio Luciano; Himbert, Dominique; Urena-Alcazar, Marina; Salgado-Fernandez, Jorge; et al. (Open heart, 2021)
BACKGROUND: The Toronto Aortic Stenosis Quality of Life Questionnaire (TASQ) is a validated instrument for assessing quality of life (QoL) in patients with severe aortic stenosis (AS). In this study, we evaluated health status outcomes, based on the TASQ, in patients with severe AS undergoing transcatheter aortic valve replacement (TAVR) or surgical aortic valve replacement (SAVR). METHODS: The TASQ registry was a prospective observational registry. Patients with severe AS from nine centres in Europe and one in Canada underwent either SAVR or transfemoral TAVR. Patients completed the TASQ, Kansas City Cardiomyopathy Questionnaire and Short Form-12 V.2 prior to the intervention, predischarge, and at 30-day and 3-month follow-ups. Primary end point was the TASQ score. RESULTS: In both the TAVR (n=137) and SAVR (n=137) cohorts, significant increases were observed in all three scores. The overall TASQ score improved as did all but one of the individual domains at 3 months after the intervention (p<0.001). TASQ health expectations were the only domain which worsened (p<0.001). Across TASQ subscores, significant changes were evident from the time of discharge in the TAVR and 30-day follow-up in the SAVR cohort. In a categorical analysis of the TASQ, 39.7% of the TAVR group and 35.0% of the SAVR group had a substantially improved health status at 3 months compared with baseline. CONCLUSIONS: The TASQ captured changes in QoL among patients with severe AS who were treated with TAVR or SAVR. QoL improved substantially after either intervention, as indicated by changes in the TASQ overall score at 3 months. TRIAL REGISTRATION NUMBER: NCT03186339.
Keywords: Kanada; Follow-Up Studies; prospektivní studie; aortic valve stenosis; Aortic Valve Stenosis; healthcare; senioři nad 80 let; Morbidity; průzkumy a dotazníky; Humans; lidé; Canada; následné studie; Health Status; Aged, 80 and over; Surveys and Questionnaires; Female; Male; Prospective Studies; aortic diseases; zdravotní stav; Transcatheter Aortic Valve Replacement; Europe; kvalita života; mužské pohlaví; Aged; aortální chlopeň; Quality of Life; quality of healthcare; ženské pohlaví; outcome assessment; Evropa; morbidita; aortální stenóza; transkatetrální implantace aortální chlopně; heart valve prosthesis implantation; Aortic Valve; Postoperative Period; pooperační období; senioři